Expressive Speech Acts in Do Revenge (2022): A Pragmatic Analysis - Irianto, Dila Najwa Sofia; Heraeni, Indi; Hadiyansyah, Dhuha; Amalia, Almira (APLIKATIF: Journal of Research Trends in Social Sciences and Humanities, 2025)
Previous studies on expressive speech acts in movies have primarily focused on identifying and classifying types of expressions, with limited attention to their pragmatic functions in contemporary teenage narratives. Moreover, the movie Do Revenge (2022) has not yet been examined from a linguistic or pragmatic perspective, indicating a research gap in the study of expressive speech acts in modern cinematic discourse. To address this gap, this study investigates the types and forms of expressive speech acts used by the characters in the film based on Searle’s (1976) speech act theory. Employing a descriptive qualitative method, the study addresses two research questions concerning the types of expressive speech acts found in the film and the ways these acts are realized in the dialogues. The findings identify six types of expressive speech acts, namely greeting, apologizing, thanking, expressing attitudes, wishing, and congratulating. In total, 55 expressive utterances were found, consisting of 51 direct and 4 indirect speech acts. Greeting appeared as the most dominant type, followed by apologizing and thanking. These findings indicate that expressive speech acts play an important role in representing emotional openness and interpersonal interaction among teenage characters. This study contributes to pragmatic research by demonstrating how expressive speech acts function as interactional resources that shape emotional expression and interpersonal dynamics in teenage film discourse.